Sosialisasi Manajemen Parenting dalam Pendampingan Belajar Anak di Rumah oleh Orang Tua: Socialization of Parenting Management in Supporting Children's Learning at Home by Parents - Aprilia, Yohanita Uniyatri; Rohmah, A’isah Maudy Nur; Amalia, Amanda Nur; Rosadah, Haryani Amrina; Wulandari, Putri; Sunardi, Andri Dwi; Putri, Ramadhina Suci Amanda; Indrasetianingsih, Artanti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The role of parents in children's learning process is vital. In the Merdeka Belajar Curriculum, parents are the key to creating an ideal and sustainable learning environment by actively participating in the child's learning process. In line with its implementation, parents often experience difficulties in assisting children's learning, such as difficulties in getting children to focus, be interested, and understand the material being taught. Lack of understanding about parenting management is one of the reasons for this problem. Therefore, parenting management was socialized to assist children's learning at home at SDN Kandangan, Krembung Sub-district, Sidoarjo Regency. This activity aims to increase parents' understanding of the application of parenting knowledge in learning with children. There are three stages in the implementation of this activity: planning, implementation, and evaluation. The method used is descriptive analysis. Data collection techniques were carried out by distributing pre-test and post-test questionnaires. The data was then processed using the Wilcoxon test. The results of the Wilcoxon test obtained a significant value of 2.736x10-6 (p <0.05). Thus, it was concluded that there was a real difference in understanding before and after the activity. This understanding of parenting is expected to improve the quality of education, especially at SDN Kandangan.